DAMPAK HASIL PELEDAKAN DENGAN DETONATOR ELEKTRONIK MENGGUNAKAN METODE SEGMENTASI DAN NON-SEGMENTASI - Handayana, Raden Haris; Alghifari, Mohamad Rifki; Salahudin, Sani; Carlo, Nasfryzal (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Sebuku Tanjung Coal, a mining company, has a blasting location close tobuilding structures. This building is included in the Class 2 building on SNI 7571:2010 with a maximum peak vector sum (PVS) value of 3 mm/s or peak particle velocity (PPV) value of 3 - 7 mm/s at the frequency of 0-100 Hz. Several critical areas are located between 200 and 700 meters from the blasting location. The used initiation system is Hanwha Electronic Blasting System 2nd Generation (HEBS II), which uses HiMex 70 (emulsion) as an explosive type. In this paper, the tie-up design of blasting uses segment and non-segment methods to compare the results of blasting using the two methods. Based on 16 compared data points, the vibration results obtained using segment and non-segment had a value range of 2,767-15,102 mm/s. The average result of the digging time using the segment method is 10.9 seconds, while the non-segment method takes 10.3 seconds. The average size of fragmentation (D80) with the segment method is 49.1 cm, while the non-segment method is 45.4 cm.